Noninvasive Assessment of Cardiopulmonary Hemodynamics Using Cardiovascular Magnetic Resonance Pulmonary Transit Time - Martin Segeroth; David Jean Winkel; Beat A. Kaufmann; Ivo Strebel; Shan Yang; Joshy Cyriac; Jakob Wasserthal; Michael Bach; Pedro Lopez-Ayala; Alexander Sauter; Christian Mueller; Jens Bremerich; et al. (International Journal of Biomedical Imaging)
Conclusion: CMR-derived PTT is a readily obtainable hemodynamic parameter. It is elevated in patients with DD and moderate to severe MVR. Low PTT values make the presence of DD and MVR—as assessed by echocardiography—unlikely.